Assessment of the Campus Clientele Satisfaction Management in Frontline Services in CSU Aparri - Sales, Cedric; Dirain, Estela (International Journal of Arts, Sciences and Education, 2024)
The paper & pen based method to gather the feedbacks of the customer or clientele that are prone to inefficiencies, errors, and delays, requiring substantial time and effort to maintain. The university's capacity to make prompt, well-informed judgments and adjust to changing conditions is hampered by this inconsistent approach. The project titled "Assessment of the Campus Clientele Satisfaction Management System (CSU-CCSM) in Frontline Services in CSU Aparri" is a new paradigm for Cagayan State University-Aparri, that combines modern customer-focused tactics with traditional educational principles. The system is designed The Agile Development model was selected as the development paradigm for this study, and it was applied within the context of the System Development Life Cycle (SDLC). PHP and MySQL were used in the system's development, along with a proprietary development methodology, Microsoft Visual Studio Code serving as the code editor and XAMPP serving as the local development environment. HTML, CSS, Bootstrap, JavaScript, and HTML were used for front-end development and styling. The CSU-CCSM offers Real-time reporting tools, faster data gathering procedures, and user-friendly digital interfaces. With the move from paper-based processes to an advanced digital platform, CSU hopes to transform how it evaluates, analyzes, and reacts to stakeholder feedback. The transformation not only shows CSU's commitment to innovation, but also its commitment to creating a responsive, inclusive environment where stakeholders' concerns are understood, heard, and promptly taken into consideration.